(untitled) (CIPEEX, 2026)
Introduction: Urinary incontinence (UI) is the involuntary loss of urine, more common in elderly women, although it is not a natural part of aging. In Brazil, up to 72% of older women may be affected; however, a lack of awareness and low demand for treatment hinder early diagnosis and intervention. Objective: This study aims to conduct an integrative review and report the risk factors, prevalence, challenges, and impacts of UI in elderly women, emphasizing the importance of prevention and appropriate management in Primary Health Care (PHC). Method: This is an integrative literature review, with searches conducted in the MEDLINE, SciELO, Google Scholar, and LILACS databases, considering articles published between 2020 and 2025, in Portuguese and English, during the period of August to September 2025, focusing on UI in elderly women. Results: The studies revealed that factors such as advanced age, female sex, obesity, multiparity, inadequate diet, and metabolic or neurological diseases are associated with UI. Despite its high prevalence, underreporting is common due to stigma and lack of information. In hospital settings, palliative approaches prevail, with little emphasis on prevention and rehabilitation, which increases patients’ vulnerability. Conclusion: It is concluded that UI requires a multidisciplinary approach, with the strengthening of PHC, professional training, and public policies focused on prevention, education, and rehabilitation. These actions are essential to improve the quality of life of elderly women, especially in the context of population aging.